(3SeGJ Gdaf GdHOGFi ai eNJGQGJ ef CYeGd GdQSe h GdJUhjQ GdMOjK h GdeYGUQ ceONd dJOQjS GdQSe (B: s (3OQGSI JLQjHjI (B= Primitive art characteristics in the selections of modern and contemporary painting and drawing work as an approach to teach drawing , Experimental study / s - (3OGdjG CTQa Ydi UGdM s; (3CTQa ESeGYjd GdYQjfi (B: s; (3ZGOI fYeGf LeYI (B: s ((3GdbGgQI (B: s (3OGdjG CTQa Ydi UGdM (B: s, 2016)
(3CgOGa GdHMK(B: (3ESJNdGU eLehYI ef SeGJ Gdaf GdHOGFi ai eNJGQGJ CYeGd afGfi GdQSe h GdJUhjQ GdMOjK h GdeYGUQ(B. (3EfJGL QShe afjI ef NdGd OQGSI CYeGd afGfi GdQSe h GdJUhjQ GdMOjK h GdeYGUQ GdPjf ESJdgehG CYeGdge ef SeGJ Gdaf GdHOGFi dEfJGL CYeGd JUhjQjI dYjfI GdHMK(B. (3JgOa GdOQGSI Gdi EjLGO eOGNd dJOQjS GdQSe dWdGH GdaQbI GdQGHYI HbSe GdJQHjI GdafjI HcdjI GdJQHjI GdfhYjI ai VhA eNJGQGJ ef CYeGd GdQSe h GdJUhjQ GdMOjK h GdeYGUQ GdeSJdgeI ef Gdaf GdHOGFi(B. (3CgejI GdHMK(B: (3jSge GdHMK ai JOQjS eGOI GdQSe ef NdGd EKQGA NHQGJ GdWGdH(B/ (3GdeYde GdeYQajI(B: (3HOQGSI Gdaf GdHOGFi h GdJYQa Ydi CgejI GdQShe GdeSJdgeI ef Gdaf GdHOGFi YfO afGfi GdQSe h GdJUhjQ GdMOjK h GdeYGUQ(B: (3dJUHM efWdbkG dEKQGA GdacQ GdEHJcGQi dOjg(B. (3jYed GdHMK Ydi JMOjO GdSeGJ(B: (3h GdedGeM(B: (3h GdMdhd h GdeYGdLGJ GdafjI GdJTcjdjI h GdCSGdjH GdafjI h GdJYHjQjI (B:(3dCYeGd afGfi GdQSe h GdJUhjQ GdMOjK h GdeYGUQ GdJi GSJdgeJ ef Gdaf GdHOGFi(B. (3jSge gPG GdHMK ai JHUjQ GdegJejf HGdaf GdJTcjdi YGeI h GdWGdH GdeYde NGUI(B: (3HEecGfjI GdCSJdgGe ef Gdaf GdHOGFi HeOGNdg GdeJfhYI YfO afGfi GdQSe h GdJUhjQ h GdJi JcTa Yf YdGbGJ LOjOI h JfXjeGJ eSJMOKI JKQi GdQDjI GdafjI(B: (3h JJjM aQUI ddJLQjH dOi eeGQS h OGQS Gdaf(B: (3GdCeQ GdPj jSGYO Ydi HdhQI EJLGg afi jMed ai CYeGdg edGeM eejRI JTLY Ydi GdEHOGY h Gdejd fMh GdJYHjQ GdJdbGFis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJUhjQs; (3GdQSes; (3Gdaf GdHOGFis